PERAN KOMITMEN ORGANISASI DALAM MEMODERASI PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Alminanda, Putri; Marfuah, Marfuah (Jurnal Analisis Bisnis Ekonomi, 2018)
The main objective of this study is to examine the role of organizational commitment variable in moderating the influence of human resource competence, utilization of information technology and internal control system on the quality of regional financial report in Bantul Regency. The data collection of this study using questionnaires. Questionnaire submitted to 96 of employees working in accounting/finance in Bantul Regency. Number of questionnaires returned and filled in completely are 90. Based on the results of hypothesis testing with moderated analysis regression (MRA) is summarized as follows: (1) internal control system and utilization of informati technology have a significant positive effect on the quality of regional government financial report and (2) organizational commitment strengthen internal control system and utilization of information technology to the quality of regional government financial report . While the competence of human resources has no significant effect on the quality of regional government financial report.